Gut microbiota contributes to the methionine metabolism in host - Wu, Xiaoyan; Han, Ziyi; Liu, Bingnan; Yu, Dongming; Sun, Jing; Ge, Liangpeng; Tang, Wenjie; Liu, Shaojuan (Frontiers in Microbiology, 2022)
Methionine (Met) metabolism provides methyl groups for many important physiological processes and is implicated in multiple inflammatory diseases associated with the disrupted intestinal microbiota; nevertheless, whether intestinal microbiota determines Met metabolism in the host remains largely unknown. Here, we found that gut microbiota is responsible for host Met metabolism by using various animal models, including germ-free (GF) pigs and mice. Specifically, the Met levels are elevated in both GF pigs and GF mice that mainly metabolized to S-adenosine methionine (SAM) in the liver. Furthermore, antibiotic clearance experiments demonstrate that the loss of certain ampicillin- or neomycin-sensitive gut microbiota causes decreased Met in murine colon. Overall, our study suggests that gut microbiota mediates Met metabolism in the host, and highlighting gut microbial regulation is a prospective target for the treatment of Met metabolism-related diseases.